TYPES OF INTELLECTUAL PROPERTY RIGHTS IN THE UNITED KINGDOM - Kmetyk, Khrystyna; Beluga, Yuliia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: to study the types of intellectual property rights in the United Kingdom (in the following – UK) and analyse the procedures of their protection under the effective UK legislation. The methodological basis of the study comprises general scientific, philosophical, analysis and special methods. Results: the authors studied such types of intellectual property rights in the UK as patents, copyright, registered and unregistered designs, trademarks and trade secrets and analysed the procedures of their protection under the effective UK legislation. Discussion: researching in details such categories of the intellectual property in the UK as patents, copyright, registered and unregistered designs, trademarks and trade secrets, analising the procedures of their protection under the effective UK legislation.